PENGARUH APLIKASI BEBERAPA KONSENTRASI PACLOBUTRAZOL DAN KOH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN UBI KAYU (MANIHOT ESCULENTA CRANTZ) - Aritonang, Prasasti Dame; Ardian, Ardian; Setiawan, Kukuh (Politeknik Negeri Lampung., 2019)
This study aimed to evaluate the effect of paclobutrazol and KOH application through leaf togrowth and production of cassava. This study was conducted from March 2017 to October 2018 in an Integrated Field Universityof Lampung. The treatmens was arranged factorially (4 x 4) in a complete randomized block design with 4 replications be avowed as group. The main factor were paclobutrazol consist of P1 = 0 ppm (control, no treatment), P2 = 400 ppm, P3 = 500 ppm and P4 = 600 ppm. The second factor were KOH consist of K1 = 0% (control, no treatment), K2 =0,5%, K3 = 1% and K4 = 1,5 given a week after paclobutrazol?s application. This study used cassava cutting varieties of kasesart. Observation variables were plant height, number of books, number of fresh leaves, fresh weight of leaves, dry weight of leaves, fresh weight of stem, dry weight of stem, fresh weight of tubers, dry weight of tubers. Data of each treatments were calculated its mean value and tested homogeneity. Homogeneous data were analyzed variance and followed by the smallest real difference testat level 5%.The study?s result showed that paclobutrazol application had inhibited effect the vegetative growth of plant height, number of nodes, fresh and dry weight of stem cassava plants. Application of KOH had a significant effect only on number of fresh leave at 13 week after planted. The interaction of paclobutrazol and KOH treatment had a significant effect on leaf dry weight.